2007
DOI: 10.1007/s10903-007-9105-3
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Need for Access to Culturally and Linguistically Appropriate HIV/AIDS Prevention for Latinos

Abstract: This article reports a comprehensive national needs assessment of Latinos' access to HIV/AIDS prevention and education services in 14 cities throughout the United States and Puerto Rico. Interviews and focus groups were conducted with Latinos who were HIV-positive and at risk for HIV infection. The study explored risk behaviors, access to health care services, and exposure to HIV prevention messages. Differences in predictors of risk behaviors were noted by sex. For women, increased age, being married, foreign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Rios-Ellis et al (2008, p.456) affirmed that designing culturally and linguistically appropriate interventions to reduce HIV/AIDS in Hispanic/Latino adolescent "requires an understanding of the many different perceptions, attitudes, and behaviors that deeply influence the Latino culture and values." Effective Latino HIV interventions must employ culturally appropriate methods such as the storybased "fotonovelas" and "radionovelas" (Rios-Ellis et al, 2008). Spanish speaking trainers should conduct interventions at schools, community health centers, and community-based organizations in order to positively improve adolescent's HIV knowledge, which in turn lessens HIV/AIDS risk behaviors among Hispanic/Latino adolescents (Rios-Ellis et al, 2008).…”
Section: Evidence-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rios-Ellis et al (2008, p.456) affirmed that designing culturally and linguistically appropriate interventions to reduce HIV/AIDS in Hispanic/Latino adolescent "requires an understanding of the many different perceptions, attitudes, and behaviors that deeply influence the Latino culture and values." Effective Latino HIV interventions must employ culturally appropriate methods such as the storybased "fotonovelas" and "radionovelas" (Rios-Ellis et al, 2008). Spanish speaking trainers should conduct interventions at schools, community health centers, and community-based organizations in order to positively improve adolescent's HIV knowledge, which in turn lessens HIV/AIDS risk behaviors among Hispanic/Latino adolescents (Rios-Ellis et al, 2008).…”
Section: Evidence-based Interventionsmentioning
confidence: 99%
“…Effective Latino HIV interventions must employ culturally appropriate methods such as the storybased "fotonovelas" and "radionovelas" (Rios-Ellis et al, 2008). Spanish speaking trainers should conduct interventions at schools, community health centers, and community-based organizations in order to positively improve adolescent's HIV knowledge, which in turn lessens HIV/AIDS risk behaviors among Hispanic/Latino adolescents (Rios-Ellis et al, 2008). Also, program developers must address Hispanic/Latino cultural values such as familialism, "machismo", "marianismo", allocentrism, fatalism, power distance, personal space, time orientation, and gender roles" to design interventions that promote Hispanic/Latino parent-adolescent communication as a mean for HIV/AIDS risk reduction strategy among adolescents (Benavides, Bonazzo, & Torres, 2006, p. 92).…”
Section: Evidence-based Interventionsmentioning
confidence: 99%
“…To further clarify HIV risks of Hispanic subgroups and to identify possible strategies for prevention, surveillance data need to be complemented by information on the social determinants contributing to the acquisition or transmission of HIV infection among foreign-born Hispanics (CDC, 2007a) Prior research has shown that cultural factors can shape the HIV epidemic among Hispanics in the U.S., and can either increase or reduce the risk of HIV infection (Marín, 2003). For example, adherence to the gender role of machismo, in which Hispanic men prove their masculinity through power and dominance, can lead to risky sex behaviors such as having multiple sex partners of unknown HIV status, engaging in unprotected sex with women or men, and using sexual coercion (Perez-Jimenez et al, 2009;Rios-Ellis et al, 2008;Weidel et al, 2008). However, machismo may also have the potential for promoting HIV prevention because of 1.…”
mentioning
confidence: 99%
“…Gender-based social roles associated with these cultural concepts and values can impede the discussion of sexual issues and the negotiation of sexual safety by women with their male partners (Marín, 2003). Because of the diversity of Hispanic peoples and cultures in the U.S., more detailed research is needed on their varied cultural beliefs and values, and how these factors and the particular circumstances of different Hispanic subgroups affect their HIV risks and protective behaviors (Rios-Ellis et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation